Low-intensity pulsed ultrasound improves osseointegration of dental implant in mice by inducing local neuronal production of αCGRP. (July 2020) - Jiang, Yixuan; Yuan, Ying; Xiong, Yi; Wang, Bin; Guo, Yanjun; Gong, Ping; Zhang, Liang
Highlights: LIPUS promotes osseointegration of dental implant. LIPUS enhances osseointegration partly through activation of αCGRP. αCGRP deficiency impedes the process of osteogenesis. LIPUS combined with αCGRP may be a novel approach to enhance osseointegration. Abstract: Objective: This study aimed to explore the effect of Low-intensity pulsed ultrasound (LIPUS) on implant osseointegration and elucidate the role of α-calcitonin gene-related peptide (αCGRP) in this process. Design: In vivo, αCGRP +/+ (Wild-type model) mice and αCGRP -/- (Knock-out model) mice with implants immediately placed in the maxillary first molars extraction sockets were treated with LIPUS. We detected details of peri-implant bone tissues by micro-CT, real-time PCR and histological analysis. In vitro, αCGRP +/+ and αCGRP -/- dorsal root ganglia (DRG) neurons were cultured and exposed to LIPUS. Then conditioned media from these neurons were collected and added to osteoblasts to analyze cell differentiation, mineralization and proliferation by real-time PCR, alkaline phosphatase (ALP) and cell counting kit‐8 (CCK‐8) assay. Besides, ELISA was performed to determine the effect of LIPUS on the αCGRP secretion in neurons. Results: In vivo tests revealed that αCGRP -/- mice displayed worse osseointegration when compared to αCGRP +/+ mice. LIPUS could enhance implant osseointegration in αCGRP+/+ mice but had little effect on αCGRP -/- mice. Meanwhile, αCGRP was elevated during the osseointegration with LIPUS treatment. In vitro, LIPUS promoted αCGRP secretion in DRG neurons, thereby enhanced osteogenic differentiation and mineralization of osteoblasts. Also we proved that the effects of LIPUS was duty cycle-related and LIPUS of 80% duty cycle had the strongest impacts. Conclusions: Our findings demonstrated that LIPUS could enhance osseointegration of dental implant by inducing local neuronal production of αCGRP, providing a new idea to promote peri-implant osseointegration and bone regeneration.